2000
DOI: 10.1046/j.1420-9101.2000.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of ecosystem processes: growth rate and elemental stoichiometry of a key herbivore in temperate and arctic habitats

Abstract: Understanding the reciprocal interactions between the evolved characteristics of species and the environment in which each species is embedded is a major priority for evolutionary ecology. Here we use the perspective of ecological stoichiometry to test the hypothesis that natural selection on body growth rate affects consumer body stoichiometry. As body elemental composition (nitrogen, phosphorus) of consumers influences nutrient cycling and trophic dynamics in food webs, such differences should also affect bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
152
10
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(184 citation statements)
references
References 46 publications
18
152
10
1
Order By: Relevance
“…A low P content is also consistent with the slow growth of Daphnia observed in Lake Redon, which would require less RNA and therefore lower P content according to the growth rate hypothesis (Main et al 1997). In contrast, in other extreme habitats such as Arctic lakes, Daphnia of the same group have been found to have a higher P content associated with a higher growth rate, which has been attributed to an adaptation of the short growing season (Elser et al 2000a). …”
Section: Discussionsupporting
confidence: 62%
“…A low P content is also consistent with the slow growth of Daphnia observed in Lake Redon, which would require less RNA and therefore lower P content according to the growth rate hypothesis (Main et al 1997). In contrast, in other extreme habitats such as Arctic lakes, Daphnia of the same group have been found to have a higher P content associated with a higher growth rate, which has been attributed to an adaptation of the short growing season (Elser et al 2000a). …”
Section: Discussionsupporting
confidence: 62%
“…The fact implies that these consumers often have to cope with stoichiometrically unbalanced food (Urabe and Sterner 1996, Denno and Fagan 2003, Schade et al 2003. Among nutrient elements, P is closely associated with the growth of heterotrophic organisms (Elser et al 2000b) and often limited nutrients in aquatic ecosystems Elser 2002, Elser et al 2007). Consumer species with higher body P content would therefore grow faster when the P content of food is high (Main et al 1997, Elser et al 2000b), but they are likely to be more vulnerable to P deficiency in the food especially in aquatic habitats Hessen 1994, Sterner and.…”
Section: Introductionmentioning
confidence: 99%
“…Among nutrient elements, P is closely associated with the growth of heterotrophic organisms (Elser et al 2000b) and often limited nutrients in aquatic ecosystems Elser 2002, Elser et al 2007). Consumer species with higher body P content would therefore grow faster when the P content of food is high (Main et al 1997, Elser et al 2000b), but they are likely to be more vulnerable to P deficiency in the food especially in aquatic habitats Hessen 1994, Sterner and. Indeed, Seidendorf et al (2010) showed that among Daphnia, key herbivore consumers in lakes and ponds, the species with higher growth rates under favorable food conditions decreased their growth rates by greater degrees when fed low P food.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms at the cellular level have received increased attention in ecological studies on thermal adaptation and growth rate in invertebrates (Elser et al 1996(Elser et al , 2000. A crucial question is how animals cope with the need for high growth rates due to short seasons in cold areas, i.e.…”
Section: Introductionmentioning
confidence: 99%